The Balance of Trade, the Terms of Trade, and the Real Exchange Rate : An Intertemporal Optimizing Framework. (IMF Working Papers; Working Paper ;, 1988)
This paper uses an intertemporal optimizing model of a small open economy to analyze how terms of trade changes affect real exchange rates and the trade balance. We consider temporary current, anticipated future, and permanent changes in the terms of trade. The results suggest that the relationship between the terms of trade and the current account (the so-called Harberger-Laursen-Metzler effect) may be quite sensitive to whether or not the model incorporates nontraded goods. Thus, the real exchange rate may be an important variable through which terms of trade shocks are transmitted to the current account.